Berani Hijrah Community as a Catalyst for the Revitalization of Islamic Values in Tanjung Morawa - Annisa Dea Mudrika; Laila Rohani (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
The hijrah community represents a growing socio-religious phenomenon among Muslim youth. The Berani Hijrah Community in Tanjung Morawa functions as a platform for Islamic guidance and personal development for adolescents. This study aims to analyse the role of the community in revitalising Islamic values through historical dimensions, religious programs, and social activities. The research employs a qualitative approach through field-based methods, including in-depth interviews, participant observation, and document analysis. The findings indicate that the community plays a significant role in shaping religious behaviour, particularly in strengthening daily worship practices, fostering Islamic identity among youth, and encouraging active participation in community-based da’wah through structured religious programs and social engagement activities. These findings demonstrate that the Berani Hijrah Community contributes to the revitalisation of Islamic values by integrating religious teachings with contemporary youth culture and social interaction.